Studi kasus intervensi fisioterapi pada lansia dengan demensia dengan senam otak dan terapi musik untuk meningkatkan kualitas tidur - Ayu Permata; Rere Mauliyah (Jurnal Ilmu Kesehatan Abdurrab, 2023)
Dementia is a disorder that occurs in the brain so that patients experience memory disorientation. In the elderly who experience dementia, it is also possible to experience difficulty sleeping due to damage to the sleep wake cycle in the brain. This study was conducted to determine the effect of providing Brain Gym therapy and music therapy to improve sleep quality in the elderly with dementia. The measuring instrument used to determine the quality of elderly sleep is the Pittsburgh Sleep Qualty Index (PSQL). The research subject consisted of 1 patient with dementia who experienced sleep disturbances. The study was conducted for 9 times therapy (T1-T9) at the patient's home. After being given 9 times of therapy with the provision of Brain Gym and music therapy, the initial therapy results obtained a total score of 14 and the final therapy 4 with a total interpretation, if the value â‰¤5 = good sleep quality and if the value >5 = poor sleep quality. The results of this study indicate that the administration of Brain Gym and Music Therapy can improve sleep quality in the elderly who experience dementia.